Reestructuración comercial administrativa de la empresa Clínica Santa Catalina S.A.S Análisis de los términos de intercambio entre Colombia y Estados Unidos a partir del Tratado de Libre Comercio (TLC) (2017)
This paper analyzes the trade dynamics between Colombia and the United States, an analysis of the behavior of the terms of trade and the purchasing power of Colombian exports before and after the entry into force of the Free Trade Agreement (2012). What is sought in this project is to confront the theory of Singer and Prebisch on the "deterioration of the inequality of the terms of trade" which indicates that there is a disparity in international trade between developed and undeveloped countries caused by the structure Countries For the development of this work the calculation of the indices and terms of trade of exports and imports was carried out giving a glance at the evolution of these in the commercial relation. The results show that the entry into force of the free trade agreement Colombia has been prejudiced in the purchasing power of Colombian exports in the US market, demonstrating that it is necessary to renegotiate issues of this treaty.